2021
DOI: 10.1016/j.celrep.2021.109133
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus drugs that inhibit SARS-CoV-2 papain-like protease synergize with remdesivir to suppress viral replication in cell culture

Abstract: Hepatitis C virus drugs that inhibit SARS-CoV-2 papain-like protease synergize with remdesivir to suppress viral replication in cell culture Graphical abstract Highlights d Several HCV protease-inhibitor drugs inhibit SARS-CoV-2 M pro and/or PL pro d These HCV drugs also inhibit SARS-CoV-2 replication in Vero and/or human cells d HCV drugs that inhibit PL pro synergize with remdesivir to inhibit SARS-CoV-2 d HCV drugs that selectively inhibit M pro are not synergistic with remdesivir

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 54 publications
2
82
1
1
Order By: Relevance
“…EC 50 s against SARS-CoV-2 were in the micromolar range, with the lowest EC 50 s (9 and 15 μM for simeprevir in A549-hACE2 and Vero E6 cells, respectively) approaching the EC 50 of remdesivir (0.1 and 2.5 μM in A549-hACE2 and Vero E6 cells, respectively); EC 50 s of remdesivir were in line with previously reported results ( 30 32 , 35 , 36 ). However, EC 50 s of PIs against SARS-CoV-2 were higher than the EC 50 s against HCV.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…EC 50 s against SARS-CoV-2 were in the micromolar range, with the lowest EC 50 s (9 and 15 μM for simeprevir in A549-hACE2 and Vero E6 cells, respectively) approaching the EC 50 of remdesivir (0.1 and 2.5 μM in A549-hACE2 and Vero E6 cells, respectively); EC 50 s of remdesivir were in line with previously reported results ( 30 32 , 35 , 36 ). However, EC 50 s of PIs against SARS-CoV-2 were higher than the EC 50 s against HCV.…”
Section: Discussionsupporting
confidence: 91%
“…Inhibitor efficacy can be improved by combination treatments with synergistic and thus drug-saving effects as reported here for the combination of remdesivir with the macrocyclic PIs simeprevir, paritaprevir, or grazoprevir in Vero E6 cells and with simeprevir or grazoprevir in A549-hACE2 cells. Synergism was recently suggested for the combination of remdesivir with simeprevir ( 35 , 36 ) or grazoprevir ( 36 ) in short-term assays in Vero E6 cells ( 35 , 36 ) and human embryonic kidney (HEK293T) cells ( 36 ). Our extensive results in Vero E6 and A549-hACE2 cells using short-term drug interaction assays demonstrated that the mode of interaction between PI and remdesivir depended on the PI structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple in vitro studies demonstrated that, at the nanomolar concentration, remdesivir is effective against SARS-CoV-2 infection [123][124][125]. Interestingly, a recent in vitro study revealed that a combination of remdesivir with repurposed hepatitis C virus (HCV) drugs was 10 times more effective at inhibiting SARS-CoV-2 [126]. In addition, in non-human primate studies, remdesivir treatment had a clinical benefit as reflected by reduced viral load and lung damage [127].…”
Section: Remdesivirmentioning
confidence: 99%
“…Indeed, combination treatment with remdesivir plus baricitinib (a Janus kinase inhibitor) was superior to remdesivir alone in improving clinical status and recovery among COVID-19 patients (Kalil et al, 2021). A multi-center study reported that four approved drugs against hepatitis C that inhibit the papainlike protease of SARS-CoV-2 can enhance the antiviral effects of remdesivir by ten-fold in vitro (Bafna et al, 2021). Synergy between remdesivir and emetine has also been documented (Choy et al, 2020).…”
Section: A B D Cmentioning
confidence: 99%